Complications of chronic otitis media: a retrospective analysis of 1293 cases - Karakaş, Mustafa; Hüseyin Balıkçı, H.; Haluk Özkul, M.; Çelebi, Şaban; Bayram, Özlem; Alper Bayram, A. (ENT Updates, 2014)
Objective: To evaluate the clinical signs and symptoms, diagnosis, treatments, outcomes, distribution and incidence of the complications of chronic otitis media (COM). Methods: This retrospective study analyzed the clinical and operative findings of 1293 patients with COM, including 39 patients with complications of COM. We compared the surgical techniques, incidence and management of complications and morbidity and mortality rates with those reported in the relevant literature. Results: Of the patients with complications, 23 were male and 16 were female. Eight patients (20.5%) had intracranial complications, while 31 (79.5%) had extracranial complications. Lateral sinus thrombophlebitis and labyrinthine fistula were the most common intra- and extracranial complication, respectively. Of the 39 patients with complications, 27 underwent radical mastoidectomy, including two patients who underwent simultaneous labyrinthectomy. Revision radical mastoidectomy, canal wall down tympanomastoidectomy and canal wall up tympanomastoidectomy were performed in one, six and five patients, respectively. All patients did well, and the mortality rate was 0% during a follow-up period of 46±22 months. Conclusion: Despite their reduced incidence, COM complications continue to pose a great, clinical challenge. A careful history, physical examination, effective use of imaging technology and most importantly, a greater awareness of COM complications will reduce their morbidity and mortality.